Surgical Management of an Epithelioid Hemangioendothelioma of the Superior Vena Cava Protruding into the Right Atrium. Issue 6 (3rd June 2014) - Allain, G.; Hajj‐Chahine, J.; Lacroix, C.; Tomasi, J.; Corbi, P.; Jayle, C.
Abstract Epithelioid hemangioendothelioma (EH) is a rare malignant tumor of vascular origin that often involves soft tissues and visceral organs, and less commonly, large veins. We report a case of EH of the superior vena cava protruding into the right atrium and its surgical management. doi: 10.1111/jocs.12370 (J Card Surg 2014;29:779–781)